Improving Connection Ability and Mathematical Disposition of Junior High School Students with Connecting, Organizing, Reflecting, Extending (CORE) Learning Model - Supianti , In In; Yaniawati, Poppy; Ramadhan, Adhitya Gilang; Setyaji, Muhamad; Puspitasari, Pipit (Mathematics Education Journal, 2022)
The connection ability and disposition of mathematics of junior high school students still need to be improved. This research purpose to analyze the enhancement of connection of mathematics abilities and mathematical dispositions of students who received CORE learning models and conventional learning and to analyze the correlation between the connection abilities and students’ dispositions. This study uses the embedded type Mixed Method. The population was all eighth-grade students one of the public junior high schools in Pangalengan, Bandung Regency, and the sample involved as many as 74 students. The instruments used were a mathematical connection ability test, a disposition questionnaire, an observation sheet, and an interview guide. Analysis of data used two Independent Sample t-Test and Mann Whitney test. The results showed that: 1) the improvement of the connection ability of students who received CORE learning was better than students who received conventional learning 2) the disposition of students who received the CORE learning model was better than students who received conventional learning models, 3) there was no relationship between connection ability and disposition of students using the CORE learning model. The conclusion is CORE model is effective to improve students' mathematical connection ability and mathematical disposition.DOI : https://doi.org/10.22342/jpm.16.2.17079.187-202